PENGARUH AKTIVA TETAP, HUTANG JANGKA PANJANG DAN MODAL TERHADAP LABA BERSIH PERUSAHAAN PADA PT SEMEN BATURAJA (PERSERO) Tbk - oktaviana, yana; Raharto, Tito Budi (Universitas Mitra Indonesia, 2024)
This study aims to determine how the Effect of Fixed Assets, Long-Term Debt, and Capital Against Net Profit on the Company Pt Semen Baturaja (Persero) Tbk. This study uses descriptive quantitative data with primary and secondary data sources in the form of financial statements. The sampling used is fixed assets, long-term debt, capital and net income. The results of this study indicate that the simultaneous test results (Test F) obtained F count 11,327 f table 2.90 with a significant result of 0,000 0,05 which means that Fixed Assets, Long-term Debt and Capital jointly have an effect and significant against Net Profit. While t test results (1) Fixed Assets have a value of t count 3.736 t table 2.03693 with a significant level of 0.001 0.05, which means that Fixed Assets have a positive and significant effect partially on Net Profit. (2) Long-term Debt has a value of t count -5,310 t table 2,03693 with a significant level of 0,000 0,05 which means that Long-Term Debt does not have a significant and partial effect on Net Profit. (3) Capital has a value of t count 3.143 t table 2.03693 with a significant level of 0.004 0.05, which means that capital has a significant and partial effect on Net Profit.Keywords: Fixed Assets, Long-term Debt, Capital and Net Profit.